Enhanced Performance of a Molecular Photoacoustic Imaging Agent by Encapsulation in Mesoporous Silicon Nanoparticles. Issue 27 (21st May 2018) - Kang, Jinyoung; Kim, Dokyoung; Wang, Junxin; Han, Yunho; Zuidema, Jonathan M.; Hariri, Ali; Park, Ji‐Ho; Jokerst, Jesse V.; Sailor, Michael J.
Abstract: Photoacoustic (PA) imaging allows visualization of the physiology and pathology of tissues with good spatial resolution and relatively deep tissue penetration. The method converts near‐infrared (NIR) laser excitation into thermal expansion, generating pressure transients that are detected with an acoustic transducer. Here, we find that the response of the PA contrast agent indocyanine green (ICG) can be enhanced 17‐fold when it is sealed within a rigid nanoparticle. ICG encapsulated in particles composed of porous silicon (pSiNP), porous silica, or calcium silicate all show greater PA contrast relative to equivalent quantities of free ICG, with the pSiNPs showing the strongest enhancement. A liposomal formulation of ICG performs similar to free ICG, suggesting that a rigid host nanostructure is necessary to enhance ICG performance. The improved response of the nanoparticle formulations is attributed to the low thermal conductivity of the porous inorganic hosts and their ability to protect the ICG payload from photolytic and/or thermal degradation. The translational potential of ICG‐loaded pSiNPs as photoacoustic probes is demonstrated via imaging of a whole mouse brain. Abstract : The photoacoustic response of indocyanine green (ICG) is substantially enhanced when it is sealed within rigid porous nanoparticles such as porous silicon, porous silica, or calcium silicate. The enhanced photoacoustic contrast is attributed to the low thermal conductivity of the porous hosts and their ability to protect the ICG payload against photochemical degradation.